The Use of Interactive Multimedia Material Te-Ga in Teaching Listening and Speaking Skills for Students With Special Needs - Aspah, Dzulkifli Mohd; Benjoran, Micheal Angelo (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This study aims to identify the use of interactive multimedia materials, Te-Ga, in teaching listening and speaking skills for students with special needs. Listening and speaking skills are essential language skills in the Malay language subject. The use of learning materials in the form of pictures and videos creates a static learning environment, causing students with special needs to not engage in teaching and learning sessions, resulting in low mastery levels in listening and speaking skills. Therefore, the use of interactive multimedia materials, Te-Ga, helps to increase the involvement of students with special needs in learning sessions. This study was conducted using a qualitative approach and adapted Kurt Lewin's action research model. The participants involved in the study were five Year 4 students from a Chinese National Type School in the Tamparuli district. The instruments used in the study were document analysis, observation, interviews, audio recordings, and checklists. The collected data were analyzed descriptively. The findings of the study indicate that the use of interactive multimedia materials, Te-Ga, can improve students' mastery levels in listening and speaking skills through their involvement in engaging learning sessions. Overall, this study can serve as a guide for Malay language teachers in creating effective learning environments through the use of interactive multimedia materials.